2016
DOI: 10.1002/ajoc.201600330
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, Crystallographic, and Computational Studies of Extensively Hydrogen Bonded Bilayers in Thermally Stable Adamantane Hydroperoxides

Abstract: The use of moleculari odine as ah eterogeneous catalyst for the peroxidation of adamantan-2-one with 30 % H 2 O 2 resulted in an unexpected hydroperoxydiadamantyl peroxide and oxahomoadamantan-5-one,i na ddition to the expected adamantanylb ishydroperoxide. The crystal structures of both the hydroperoxides are reported for the first time. Crystallographic studies revealed that thesep eroxides are stabilized by extensive intra-and intermolecular hydrogen bonds, which are combined in hydrogen-bonded double layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Obviously, the Diels–Alder reaction had produced the isomer with adamantyl substituents in adjacent positions as the major product (67%) while the allegedly less crowded product only formed to minor extent (12%). This result appears to be in contrast to the expectation based on steric arguments and it was suggested that attractive, noncovalent dispersion forces arising from large, polarizable substituents (dispersion energy donors, DEDs) could be important for the formation of 6 . , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the Diels–Alder reaction had produced the isomer with adamantyl substituents in adjacent positions as the major product (67%) while the allegedly less crowded product only formed to minor extent (12%). This result appears to be in contrast to the expectation based on steric arguments and it was suggested that attractive, noncovalent dispersion forces arising from large, polarizable substituents (dispersion energy donors, DEDs) could be important for the formation of 6 . , …”
Section: Introductionmentioning
confidence: 99%
“…This result appears to be in contrast to the expectation based on steric arguments and it was suggested 23 that attractive, noncovalent dispersion forces 24 arising from large, polarizable substituents (dispersion energy donors, DEDs) could be important for the formation of 6. 23,25 There is currently considerable interest in elucidating the effect of London dispersion on the structural, energetic, and chemical properties of organic, organometallic, and inorganic compounds. 23,26,27 While the influence of attractive dispersive interactions can be substantial, in particular in the gas phase, there is evidence that the effect can be attenuated by solvents.…”
Section: Introductionmentioning
confidence: 99%
“…By analogy with the oxidation of cyclohexane [64][65][66], such compounds could include mono-and di-hydroperoxide groups in their composition. For example, a scheme for the oxidation of 0 with the participation of its primary and secondary hydroperoxides is proposed [66], the formation of thermally stable 1-adamantylhydroperoxide (2d) [67] and 2,2-dihydroperoxy-adamantane (4a') is described [68,69].…”
Section: Introductionmentioning
confidence: 99%